Safer, but not safe enough - Vickers, J (MDPI, 2019)
The great divide between official analyses and economists’ views of optimal bank equity capital is not as wide as appears at first sight if the economics of risk is properly addressed. Adapting the BoE’s analysis to take account of abnormal risk conditions, a less benign view of the effectiveness of resolution regimes in systemic crisis, an international rather than domestic perspective, and a consistent approach to risk, takes one a good distance towards the economists’ view. The economic rationale for capital levels in the region of Basel III is left looking thin. It looks thinner still when, as now, price-to-book ratios are calling regulatory capital measures into question for some important banks.